Sentiment Analysis on Users' Satisfaction for Mobile Banking Apps in Malaysia - Misinem, .; Tri Basuki, Kurniawan; Mohd Zaki, Zakaria; Muhammad Aqil Azfar, Uzailee (INTI International University, 2022)
A service offered by a bank or other financial institution that enables its users to execute financial transactions remotely using a mobile device, such as a smartphone or tablet, is known as mobile banking. The bank provides many mobile banking apps in Malaysia, such as CIMBClicks, Maybank2U, etc. Data classification has become the region of interest in Data Mining research as it indicates the arising of technology's application that leads to increment data usage. In this research, collection data and experiments are conducted, and results are shown. The prepossessing is discussed and explained in quite detail, and the results are analyzed and discussed further. The dataset was compared with five algorithms: Linear Regression, Naïve Bayes, Decision Tree, Random Forest, and Support Vector Machine (SVM). The best accuracy result shows 94.37% by the Decision Tree algorithm, and Naïve Bayes obtained the worst outcome at 66%.